Computed tomography quantification of emphysema in people living with HIV and uninfected controls. Issue 1 (19th July 2018) - Ronit, Andreas; Kristensen, Thomas; Hoseth, Vilde S.; Abou-Kassem, Dalia; Kühl, Jørgen T.; Benfield, Thomas; Gerstoft, Jan; Afzal, Shoaib; Nordestgaard, Børge G.; Lundgren, Jens D.; Vestbo, Jørgen; Kofoed, Klaus F.; et al.
People living with HIV (PLWH) may be more susceptible to the development of emphysema than uninfected individuals. We assessed prevalence and risk factors for emphysema in PLWH and uninfected controls. Spirometry and chest computed tomography scans were obtained in PLWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) study and in uninfected controls from the Copenhagen General Population Study (CGPS) who were >40 years. Emphysema was quantified using a low attenuation area < −950 Hounsfield units (%LAA-950) and the 15th percentile density index (PD15) and assessed by semi-quantitative visual scales. Of 742 PLWH, 21.2% and 4.7% had emphysema according to the %LAA-950 threshold with cut-offs at 5% and 10%, respectively. Of 470 uninfected controls, these numbers were 24.3% (p=0.23) and 4.0% (p=0.68). HIV was not associated with emphysema (adjusted OR 1.25, 95% CI 0.68–2.36 for %LAA-950 >10%) by PD15 or by visually assessed emphysema. We found no interaction between HIV and cumulative smoking. Breathlessness and sputum production were more common in PLWH with emphysema, and emphysema seemed to be more prevalent in PLWH with airflow limitation. HIV was therefore not independently associated with emphysema, but the clinical impact of emphysema was greater in PLWH than in uninfected controls. Well-treated HIV infection is not associated with emphysema http://ow.ly/2IA430khHvy